Assessing the role of education managers in teacher retention: the case of community day secondary schools in phalombe district of Malawi - Kaluwa, Hartley (Mzuzu University, 2015)
Teacher attrition and turnover is one of the challenges besetting the teaching profession in Malawi. This challenge has a number of implications among them teacher shortage. The profession has been described as ‘a profession at risk’ due to the high turnover rates. Therefore, identifying the factors and understanding teachers who leave the profession, and under what conditions is important for formulating and employing strategies that target and promote teacher retention. The purpose of this study was to assess the role of education managers in promoting teacher retention in CDSSs in Phalombe district. The study sought to establish the causes of teacher attrition and turnover in Phalombe district, the impact of teacher attrition and turnover on the quality of teaching and learning in Phalombe district, strategies education managers currently use to promote teacher retention in Phalombe district and strategies that education managers can employ in order to promote teacher retention in Phalombe district. Employing a qualitative case study design guided by a blend of Hertzberg two factor theory and Open systems theory as its theoretical framework, this study was carried out in some selected Community Day Secondary Schools in Phalombe district. Findings suggest that teacher attrition and turnover in Phalombe is attributed toa plethora of factors which concern three themes namely: jobsatisfaction, working conditions and issues of staff development. Attrition and turnover have adverse impacts on quality of teaching and learning as they create shortages of teachers, high pupil-to qualified teacher ratio, and lead to stress and burnout in the teachers, demotivation and poor learner performance. However, improvements in aforementioned thematic areas could be strategies to promote teacher retention. The study concludes by asserting that promoting teacher retention requires a multi-sectoral approach.